การวิเคราะห์การทำหน้าที่ต่างกันของข้อสอบและแบบสอบด้วยกระบวนการ ดี เอฟ ไอ ที สำหรับแบบสอบคัดเลือกบุคคลเข้าศึกษาในสถาบันอุดมศึกษา วิชาภาษาอังกฤษและวิชาคณิตศาสตร์ - รักชนก ยี่สุ่นศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
This research has three main purposes. First, to analyze the differential item functioning (DIF) and differential test functioning (DTF) based on DFIT procedure for 2 subgroups ; gender and location of school. Second, to compare the discrepancy between the quality of test before and after DIF items are eliminated, in terms of reliability, validity and test information function. The last objective is to analyze the relationship between the rank of examinees total score of the original test and the test after the DIF items are eliminated. The data are the examinees item response to English and Mathematics university entrance examiniation tests in the part of multiple choice items, administered by the Ministry of the University Affairs in the first examination of the year 2000. The sample of study was 4,000 and 3,600 examinees in English and Mathematics tests, respectively. The major findings are as follows: 1. English test is differential functioning according to examinees gender and school location while Mathematics test is differential functioning according to examinees gender subgroup. Detecting differential functioning at items level according to gender subgroup is the largest number of DIF items in both English and Mathematics tests. 2. The results from comparing the discrepancy between the quality of test before and after DIF items are eliminated, are as follows: 2.1 The construct validity of the test is not significantly different from that of the original test. 2.2 The reliability of the test is slightly lower than that of the original test. 2.3 The test information function has no difference by the test that after DIF items are eliminated is slightly greater than that of the original test. 3. The results from analyzing the relationship between the rank of examinees total score before and after the DIF items are eliminated, have significant positive relationships. The Spearman rank correlation coefficient is in the range of 0.83-0.99 and 0.87-0.98 for the English and Mathematics tests, respectively.